Effects of Lignin-Derived Polycarboxylic Acids on the Properties of Waterborne Polyurethane Elastomers - Ruiqi Wang; Bing Zhou; Yanchao Zhu; Zichen Wang (International Journal of Polymer Science)
Lignin was modified by oxidation to prepare lignin-derived polycarboxylic acids (LPCAs), which can be introduced into waterborne polyurethane (WPU) elastomers through the interactions with the soft segments of WPU. The changes of water resistance, thermal and tensile properties of WPU elastomers were observed. After LPCAs were added, the water solubility of WPU elastomers was increased. Besides, the weight loss peak of the soft segments of WPU moved to the lower temperature, indicating that the decomposition of soft segments became easier and the interspace of the soft segments regions was enlarged by LPCAs. Comparing with the blank WPU elastomer, when the LPCA loading was 2.5 wt% (based on PPG-1000), the tensile stress of the LPCA-WPU materials at 100% and 300% strain increased 135.4% and 90.5% separately, and the modulus of elasticity in tension increased 383.6%. Therefore, LPCAs could serve as reinforcing fillers in WPU elastomers, which contributes to develop more functional and eco-friendly WPU materials. Moreover, the usage of lignin is broadened.